Predictors of healthcare seeking delays among children with chronic musculoskeletal disorders in Nepal - Drake G. LeBrun; Divya Talwar; Tuyetnhi A. Pham; Bibek Banskota; David A. Spiegel (Journal of Epidemiology and Global Health, 2019)
Background: Healthcare seeking behaviors among children with musculoskeletal disorders are poorly understood. We sought to analyze healthcare seeking delays among children with chronic musculoskeletal conditions in Nepal and identify predictors of clinically significant delays. Methods: A cross-sectional study was conducted at a large pediatric musculoskeletal rehabilitation center in Nepal. Baseline sociodemographic data and healthcare seeking behaviors were assessed via interviews with 75 randomly selected caregivers. Delays of at least 3 months between disease recognition and presentation to a health worker were considered clinically significant. Predictors of significant delay were assessed via multivariable logistic regression. Results: Clubfoot was the most common condition seen in the study sample (N = 33; 37%). Mean and median presentation delays were 33 months and 14 months, respectively. Sixty-seven percent of children were delayed at least 3 months and 40% were delayed at least 2 years. Caregiver occupation in agriculture or unskilled labor was associated with an increased risk of delayed presentation (adjusted OR = 4.05; 95% CI: 1.36–12.09). Conclusions: Children with chronic musculoskeletal disorders in Nepal face significant delays in accessing healthcare. This poses a major clinical problem as the delayed diagnosis and treatment of childhood musculoskeletal disorders can complicate management options and decrease long-term quality of life.